Managing Metabolic Acidosis in Chronic Renal Diseases - Suandika, Made; Woung-Ru Tang; Dewi, Pramesti (Peneliti Teknologi Teknik Indonesia, 2023)
One of the most common side effects of chronic kidney disease is metabolic acidosis (CKD). It is associated with the development of CKD and various other functional disorders. Metabolic acidosis can be a common complication associated with progressive loss of kidney function. The form can be a metabolic acidosis with a non-anion gap or metabolic acidosis with a high or mixed anion gap. Reduced kidney ability to maintain acid-base homeostasis results in acid accumulation, causing various complications such as decreased nutritional status such as wasting muscle-hypoalbuminemia, inflammation, uremic bone disease and its association with increased mortality. In addition to the side effects associated with acid retention, metabolic acidosis can also cause kidney damage, possibly through stimulation of adaptive mechanisms aimed at maintaining acid-base homeostasis in the event of decreased renal function. chronic kidney disease (CKD), and therefore offers an effective, safe and affordable reno-protective strategy. This paper will discuss the physiology and pathophysiology of acid-base homeostasis in CKD, namely the mechanism of metabolic acidosis capable of impairing kidney function, and its relation to the benefits of alkaline therapy. based on clinical trials